Natural Treatment for Animals: The Role of Medicinal Plants and Vitamins in Maintaining Health - Sh. S, Doniyorov; O, Sunnatova; Aziza, Negboyeva (American Journal of Biology and Natural Sciences, 2025)
This study evaluates the effectiveness of medicinal plants and vitamins in maintaining animal health using two primary methodological approaches: Randomized Controlled Trials (RCT) and experimental studies. The research examines the impact of medicinal plants (Aloe vera, Echinacea, Turmeric, etc.) and vitamins (Vitamin C, E, D, B12) on animal health. Positive results were obtained regarding health indicators such as immune system activity, growth rate, reproductive performance, and inflammation levels. The findings confirm the significant role of medicinal plants and vitamins in improving animal health and provide a basis for incorporating these methods into veterinary practice.